Polypodium s.s. (Polypodiaceae) in Brazil - Salino, Alexandre; Moura, Ingridy Oliveira; Sanín, David (Phytotaxa, 2019)
Polypodium s.s. is currently a fern genus with about 40 species, and still with a controversial circumscription. The Flora of Brazil online reports just one Polypodium species in Brazil. Here we confirm the occurrence of a second species of the genus in Brazil, and present a taxonomic treatment of Polypodium from this country; this includes descriptions, an identification key, diagnostic illustrations, and comments on the species. The genus is represented in Brazil by two species: Polypodium flagellare and P. kunzeanum. In addition, a lectotypification is proposed.